Co-existence of multiple strains of porcine circovirus type 2 in the same pig from China - Zhai, Shao-Lun (BioMed Central, 2011)
Pigs are often co-infected by different viral strains from the same virus. Up to now, there are few reports about co-existence of different porcine circovirus type 2 (PCV2) strains in China. The aim of this study was to evaluate it in Chinese swine herds. 118 PCV2 positive DNAs isolated from diseased pigs identified by classic PCR were re-detected using a modified differential PCR assay. The results indicated that co-existence rates of PCV2 were 32.2% (38/118) in diseased pigs and 0% (0/41) in asymptomatic pigs. Four PCV2 complete genomes were cloned from two co-infected samples and their nucleotide (nt) identities were 95%-97.3%. The phylogenetic analysis showed that four PCV2 strains were divided into different genotypes, PCV2a, PCV2b, PCV2d and PCV2e, respectively. In addition, co-existence were not detected in 41 serum samples from healthy pigs but PCV2 single infection (31.7%, 13/41) existed. These data revealed that the co-existence of different strains of PCV2 might contribute to the development of more severe clinical symptoms for pigs. This is the first report confirming the co-existence of different PCV2 strains in Chinese swine herds. Meanwhile, this study could help us to understand new infection and prevalence forms of PCV2 clinically.